2016
DOI: 10.1088/1751-8113/49/48/485201
|View full text |Cite
|
Sign up to set email alerts
|

The stabilizer group of honeycomb lattices and its application to deformed monolayers

Abstract: Abstract. Isospectral transformations of exactly solvable models constitute a fruitful method for obtaining new structures with prescribed properties. In this paper we study the stability group of the Dirac algebra in honeycomb lattices representing graphene or boron nitride. New crystalline arrays with conical (Dirac) points are obtained; in particular, a model for dichalcogenide monolayers is proposed and analyzed. In our studies we encounter unitary and non-unitary transformations. We show that the latter g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…3. However, it is necessary to work in the quasi-parabolic energy regime that is below the Dirac point [36] ( D ), obtaining the upper graph, a parabola with regions where the Maxwellian potential acts. It is worth mentioning that the region of the potential for p < −P R is not bounded above as in the graph below.…”
Section: Spatial and Spectral Decompositionmentioning
confidence: 99%
“…3. However, it is necessary to work in the quasi-parabolic energy regime that is below the Dirac point [36] ( D ), obtaining the upper graph, a parabola with regions where the Maxwellian potential acts. It is worth mentioning that the region of the potential for p < −P R is not bounded above as in the graph below.…”
Section: Spatial and Spectral Decompositionmentioning
confidence: 99%
“…Microwave resonators [25], bent waveguides with corners [26] and, in general, arrays of potential wells such as molecular structures, motivate the introduction of tight-binding Hamiltonians. We focus on planar arrays with C 3 symmetry for simplicity, although an isospectral study with dimers in three dimensions can be found in [27].…”
Section: Our Physical Systemmentioning
confidence: 99%
“…The Wigner function is the tool of choice when it comes to the quantum dynamical description of oscillatory systems in phase space that has been mostly employed with continuous variables such as position and momentum, or time and frequency. Interestingly, conjugate variables can be found also in lattices [4][5][6], where it is advantageous to employ operator methods in order to elucidate dynamical features of tight-binding models [7,8]. Moreover, peculiar connections [9,10] between a discrete position operator and the number of quanta of relativistic oscillators motivate further the definition of Wigner functions in lattices made of excitations.…”
Section: Introductionmentioning
confidence: 99%